Antinucleon spectra in the Dirac equation with scalar and vector Wood-Saxon potentials - Lisboa, R.; Malheiro, M.; Alberto, P.; De Castro, A. S. [UNESP] (AIP Publishing, 2009)
We analyze here the spin and pseudospin symmetry for the antinucleon spectra solving the Dirac equation with scalar and vector Wood-Saxon potentials. In relativistic nuclear mean field theories where these potentials have large magnitudes and opposite signs we show that contrary to the nucleon case where pseudospin interaction is never very small and cannot be treated perturbatively, for antinucleon systems this interaction is perturbative and an exact pseudospin symmetry is possible. This result manifests the relativistic nature of the nuclear pseudospin symmetry. © 2009 American Institute of Physics.
Keywords: Antinucleon; Pseudospin symmetry; Wood-saxon potentials